Spectral analysis of the emission current noise exhibited by few layer WS2 nanosheets emitter - Suryawanshi, Sachin R.; Kolhe, Pankaj S.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Ultramicroscopy, 2015)
Spectral analysis of the field emission (FE) current fluctuations has been carried out at the base pressure similar to 1 x 10(-8) mbar. The emission current stability investigated at preset value of 2 mu A is characterized by `step like fluctuation. The spectral analysis performed on a FFT (Fast Fourier Transform) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha as similar to 1.05. The estimated value of alpha implies that the current fluctuations are mainly due the various processes occurring on atomic scale like adsorption, migration, and/or desorption of the residual gas species on the emitter surface. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Current fluctuations; field emission; Noise; WS2 nanosheets